If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -7x = -77 Solving 7 + -7x = -77 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -7x = -77 + -7 Combine like terms: 7 + -7 = 0 0 + -7x = -77 + -7 -7x = -77 + -7 Combine like terms: -77 + -7 = -84 -7x = -84 Divide each side by '-7'. x = 12 Simplifying x = 12
| 9m-3=2m+46 | | 7w-12w+24=11 | | X-10=-6+2x | | 2d+19d+13d-32d=26 | | 6x-36=7 | | 6x-4=-76 | | -6x^2+9x+3=0 | | 8y-10=6y | | 5(2x-3)-x=x+1 | | 52u+9u+12u+4u-72u=75 | | 2x+8x=23.2 | | 1.07=2.3-1.2x | | -2+2x=20 | | 3n-8=2 | | x+2+8+x=20 | | 9x+2y=20 | | 61a-62a-31=-11 | | 2x+3=-1+3x | | 10x-6x-3x=2 | | -2x+3-4-4x=-10x+3+5x | | [3(7-5)-6]-[7-(2-6)]= | | 25y=15y^2 | | 6v+9=-5+3(v-6) | | 8t+3=15t+-11 | | 64v+9v-43v-28v=34 | | 8+log(8x)=29-2logx | | -8+4x=7x-41 | | 8t+3=15+-11 | | 15k-3k-k-10k+1=40 | | -3x^2-23x+30=0 | | 2(y+4)=3(y+8) | | 1000*t=9.1736 |